Criminal Liability for Forgery of Print in Polish Legislation - Rybak-Karkosz, Olivia (University of Wroclaw. Faculty of Law, Administration & Economics, 2022)
This paper aims to outline relevant legal problems of domestic legislation in aspects such as evidence difficulties, the so-called legalisation of forgery, and choosing the legal qualification of forgery of print. The doctrine for many years has postulated (and still does) the increase of protection of works of art from crimes such as forgery would increase the safety and fair trade on the art market. However, legislators tend to omit this problem. So, the other possible acts are: the Polish Criminal Code, Act of 23 of July 2003 on the Protection and Guardianship of Monuments, and Act of 16 of April 1993 on Fair Trade. Each of these acts are analysed in the context of its evidential requirements to find the most useful one. The choice of a legal action depends on whether the work of art (print) is considered a monument as in the definition included in the Act on the Protection and Guardianship of Monuments. We then compared our results with cases prosecuted in Poland.
Keywords: art forgery; forgery of art print; criminal liability of art forgery; counterfeit product marking